Real-world comparison of the last generation main balloon-expandable and self-expanding valves in patients undergoing TAVI. Does the type matter?. (25th November 2020) - Kalogeras, K; Ruparelia, N; Kabir, T; Jabbour, R; Kalantzis, C; Bei, E; Katsianos, E; Naganuma, T; Nakamura, S; Sen, S; Malik, I.S; Mikhail, G; et al.
Abstract: Background/Introduction: The balloon expandable Edwards Sapien-S3 and Ultra, and the self-expanding Medtronic Evolut-Pro and Evolut-R 34mm represent the main volume of transcatheter aortic valve implantation (TAVI) procedures conducted worldwide. Purpose: In the present study, we aim to compare the peri-procedural and one-year clinical outcomes between these last generation devices. Methods: Consecutive patients from the ATLAS (Athens-Tokyo-London Aortic Stenosis) registry, who had undergone TAVI with either the S3/Ultra or Evolut-Pro/R 34mm device, in four centers were retrospectively studied. In-hospital procedural characteristics and outcomes were recorded and compared. Kaplan-Meier estimated 1-year all-cause mortality was compared between groups. Results: In total, 692 patients (352pts treated with S3/Ultra and 340pts with Evolut-Pro/R34mm device) were included in the analysis. Baseline demographics (age, coronary artery disease risk factors, logistic Euroscore and aortic valve hemodynamics) were similar between the two groups. In terms of peri-procedural and short-term outcomes, patients treated with the Evolut-Pro/R34mm device had significantly lower peak (25.4±3.6mmHg for S3/Ultra vs 14.9±0.6mmHg for the self-expanding valves, p=0.002) and mean (10.7±0.3mmHg S3/Ultra vs 7.9±0.4mmHg Evolut PRO/R34, p<0.001) gradients at discharge. Conversely, the S3 demonstrated significantly lower rates of at least moderate residual aortic regurgitation (AR) post-operatively (0.3% vs 4.8% for S3 and Evolut-Pro/R34mm respectively, p=0.001). Interestingly, the rate of new permanent pacemaker (PPM) required after the implantation in pacemaker-free patients on baseline, was higher for the S3/Ultra cohort compared to the self-expanding valve group (17.6% vs 11.7% respectively, p=0.054), however not reaching statistical significance yet. As expected, the need for balloon post dilatation of the implanted prosthesis was less among the S3/Ultra patients (5.5% vs 26.1%, p=0.001). One-year Kaplan-Meier estimated survival was similar between the two groups (85.9% for S3 vs. 90% for Evolut-Pro/R34mm, plog-rank=0.071). Hazard ratio for all-cause mortality (Pro/R34 vs. S3/Ultra) after adjustment for gender and previous MI was similar between the groups (HR=0.73; 95% CI 0.47 to 1.14, p=0.165). Conclusions: Real life comparison of the last generation balloon expandable and self-expanding devices demonstrates similar 1-year all-cause mortality. The S3/Ultra platforms, as compared to the Evolut-Pro/R34mm, demonstrate less paravalvular leak, at the expense of higher transvalvular gradients. Long-term follow-up and future larger trials are required to establish any potential long-term difference in clinical outcomes and prognosis. Funding Acknowledgement: Type of funding source: None